High volume of endurance training impairs adaptations to 12 weeks of strength training in well-trained endurance athletes - Rønnestad, B. R.; Hansen , E. A.; Raastad, T. (European Journal of Applied Physiology, 2012)
The purpose of the present study was to compare the effect of 12 weeks of strength training combined with a large volume of endurance training with the effect of strength training alone on the strength training adaptations. Well-trained cyclists with no strength training experience performed heavy strength training twice a week in addition to a high volume of endurance training during a 12-week preparatory period (S + E; n = 11). A group of non-strength trained individuals performed the same strength training as S + E, but without added endurance training (S; n = 7). Thigh muscle cross-sectional area, 1 repetition maximum (1RM) in leg exercises, squat jump performance, and peak rate of force development (RFD) were measured. Following the intervention period, both S + E and S increased 1RM strength, thigh muscle cross-sectional area, and squat jump performance (p < 0.05), and the relative improvements in S were greater than in S + E (p < 0.05). S increased peak RFD while S + E did not, and this improvement was greater than in S + E (p < 0.05). To the best of our knowledge, this is the first controlled study to demonstrate that the strength training response on muscle hypertrophy, 1RM strength, squat jump performance, and peak RFD is attenuated in well-trained endurance athletes during a period of concurrent endurance training.